Development, conception and modulization of patient-specific miniplate in maxillofacial surgery - Ouassime Kerdoud; Rachid Aloua; Faiçal Slimani; Abdellah Boualam (Elsevier, 2021)
Due to the progress of three-dimensional (3D) modeling and design technologies, it is currently possible to easily fabricate a variety of computer-assisted and patient-specific implants. The diffusion of CAD/CAM technologies in various fields of medicine has facilitated the incorporation of these technological tools to serve and benefit maxillofacial surgery through PSI (Knoll et al., 2006) [1].Preoperative planning can be considered as a process of recognizing the patient's basics, understanding the anatomy of the patient and identifying and anticipating obstacles during the surgical procedure; all of these steps can lead us to the patientspecific implants or mini-plates (PSI*PSP) (Dong et al., 2021; Yang et al., 2020; Greenberg et al., 2021; Yang et al., 2018) [2-5].Medical imaging plays a key role in surgical planning. Clinical or surgical decisions are made following the surgeon's review of 2D imaging such as plain X-rays, computed tomography (CT) or magnetic resonance imaging (MRI). However, extracting relevant 3D anatomical relationships from 2D images for intraoperative application can be challenging, even for experienced practitioners. Intuitively, 3D reconstructions seem to have an advantage over traditional 2D images. Consequently, interest in 3D visualization techniques in surgical specialties has increased in recent years (Baan et al., 2020; Yamazaki et al., 2021) [6,7].